Colombian art : 3500 years of history - Londoño Vélez, Santiago (Bogota : Villegas Editores, 2001)
Abularach, Rodolfo ; Acuña, Luis Alberto ; Alcantara, Pedro ; Alfaro Siqueiros, David ; Alpuy, Julio ; Amaral, Jim ; de Amaral, Olga ; Antunez, Nemesio ; Arango Pérez, Débora ; Arenas Betancourt, Rodrigo ; Ariza, Gonzalo ; Arosemena, Justo ; Azout, Lydia ; Barrera, Antonio ; Barrios, Alvaro ; Bartelsman, Jan ; Borges, Jacobo ; Botero, Fernando ; Brizzi, Ary ; Bursztyn, Feliza ; Caballero, Luis ; Cajahuaringa, Milner ; Cano, Francisco Antonio ; Cardena, Michel ; Cardenas Arroyo, Juan ; Cárdenas, Santiago ; Cardoso, Maria Fernanda ; Caro Lopera, Antonio José ; Castles, John ; Correa, Carlos ; Cortés, Maria Cristina ; Cristancho, Raúl ; Cuartas, Gregorio ; Cuellar, Teresa ; Cuevas, Jose Luis ; Daza, Beatriz ; Diaz Vargas, Miguel ; Facundo, Rodrigo ; Felguerez, Manuel ; Figari, Pedro ; Fonseca, Luis ; Giangrandi, Umberto ; Giraldo, Luis Hernando ; Gomez Camuzano, Ricardo ; Gomez Jaramillo, Ignacio ; Gomez, Consuelo ; Gomez, Pedro Nel ; Gongora, Leonel ; González, Beatriz ; Granada, Carlos ; Grass, Antonio ; Grau, Enrique ; Guayasamin, Oswaldo ; Gutierrez, Alberto ; Hernandez, Manuel ; Herran, Alvaro ; Herrán, Juan Fernando ; Hoyos, Ana Mercedes ; Humberto, Aquino ; Ianelli, Arcangelo ; Jacanamijoy, Carlos ; Jaramillo, Alipio ; Jaramillo, Lorenzo ; Jaramillo, Luciano ; Jaramillo, Oscar ; Jimenez, Dario ; Lam, Wifredo ; León, Noé ; Londoño, Germán ; Lozano, Margarita ; Luna, Luis ; Mac Entyre, Eduardo ; Manzur, David ; Marquez, Judith ; Martinez Delgado, Santiago ; Martinez, José Horacio ; Martorell, Maria ; Mateus, Alfonso ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Matto, Francisco ; Mazuera, Diego ; Méjia, Norman ; Morales Sequeira, Armando ; Morelos, Delcy ; Munoz, Oscar ; Negreiros, Maria Tereza ; Negret, Edgar ; Obregon, Alejandro ; etc.
bibliog. p. 411-415
Engels
boek
Keywords: Colombia